The Effect of Tax Socialization, the Role of Tax Justice and Taxpayer Trust on Taxpayer Compliance Using Public Trust Moderation Variables - Tri Indah Wulandari (Dinasti Publisher, 2025)
This study aims to analyze the influence of Tax Socialization, Tax Fairness, and Taxpayer Trust on Taxpayer Compliance. The data were analyzed using multiple linear regression to test the relationship between independent and dependent variables. The results of the study show that the three independent variables have a significant influence on Taxpayer Compliance. Tax socialization has a positive effect, which means that the more effective the socialization carried out by the tax authority, the higher the level of taxpayer compliance. Tax fairness also has a significant effect, showing that taxpayers are more compliant if they feel that the tax system implemented is fair and non-discriminatory. In addition, taxpayers' trust in the government and tax management contributes to increased tax compliance, where taxpayers who believe that taxes are well managed tend to be more compliant.Although the regression model showed a significant influence, the value of the determination coefficient (R² = 10.2%) indicated that there were other factors outside the study that affected taxpayer compliance. Therefore, further studies are needed to identify other factors that contribute to improved tax compliance.